Effects of maturity at harvest and cultivar on agronomic performance of forage sorghum and the nutritive value of selected sorghum silages - R.N. Sonon; R. Suazo; L. Pfaff; J.T. Dickerson; K.K. Bolson (Kansas Agricultural Experiment Station Research Reports, 1991)
These studies examined the agronomic performance of 20 forage sorghum cultivars, each harvested at three stages of maturity in 1990. Whole-plant dry matter (DM) yields were highest at the late-dough stage of kernel maturity, whereas DM content and grain yields steadily increased as maturity advanced. A voluntary intake and digestion trial was conducted with 12 grain and forage sorghum silages harvested at the late-dough stage in 1989. The highest silage DM intakes and digestibilities were obtained with the high-grain yielding hybrids.
Keywords: Cattlemen' s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Forage sorghum; Cultivar; Maturity; Intake; Digestibility